Goldilocks at the dawn of complex life: mountains might have damaged Ediacaran–Cambrian ecosystems and prompted an early Cambrian greenhouse world - Fabricio Caxito; Cristiano Lana; Robert Frei; Gabriel J. Uhlein; Alcides N. Sial; Elton L. Dantas; André G. Pinto; Filippe C. Campos; Paulo Galvão; Lucas V. Warren; Juliana Okubo; Carlos E. Ganade (Scientific Reports, 2021)
Abstract We combine U–Pb in-situ carbonate dating, elemental and isotope constraints to calibrate the synergy of integrated mountain-basin evolution in western Gondwana. We show that deposition of the Bambuí Group coincides with closure of the Goiás-Pharusian (630–600 Ma) and Adamastor (585–530 Ma) oceans. Metazoans thrived for a brief moment of balanced redox and nutrient conditions. This was followed, however, by closure of the Clymene ocean (540–500 Ma), eventually landlocking the basin. This hindered seawater renewal and led to uncontrolled nutrient input, shallowing of the redoxcline and anoxic incursions, fueling positive productivity feedbacks and preventing the development of typical Ediacaran–Cambrian ecosystems. Thus, mountains provide the conditions, such as oxygen and nutrients, but may also preclude life development if basins become too restricted, characterizing a Goldilocks or optimal level effect. During the late Neoproterozoic-Cambrian fan-like transition from Rodinia to Gondwana, the newborn marginal basins of Laurentia, Baltica and Siberia remained open to the global sea, while intracontinental basins of Gondwana became progressively landlocked. The extent to which basin restriction might have affected the global carbon cycle and climate, e.g. through the input of gases such as methane that could eventually have collaborated to an early Cambrian greenhouse world, needs to be further considered.